The Effect of REACT Learning Model on Mathematics Problem Solving Ability - La Masi; La Misu; Dian Pitasari (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2022)
REACT is a development model of contextual learning, to help teachers relate learning material to the real world. This study aims to determine the effect of the REACT learning model on the mathematical problem solving abilities of junior high school students. The populations of this study were all grade VII students of SMP Negeri 2 Unaaha in the academic year 2019/2020 which was distributed in 5 classes. The sample was determined using purposive sampling technique, so that two classes were selected as samples, namely class VII1 as the experimental class and class VII2 as the control class. The research design used a posttest-only control design. The research instrument used teacher and student activity observation sheets, and tests of mathematical problem solving abilities. The observation data was collected during the learning process using the REACT learning model, while the data from the problem-solving ability test was carried out during the posttest. The results showed that there was a significant effect of the REACT learning model on the mathematical solving ability of grade VII students of Junior High Schools. The REACT learning model can develop students' creative thinking so that they can construct their own concepts and knowledge.